Hubungan Tingkat Pengetahuan Dengan Kepatuhan Minum Obat Pada Penderita Hipertensi - Farisya, Muhammad Randa; Purnomo, Slamet; Septiawan, Taufik (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Complications that occur in people with high blood pressure include stroke, aneurysm, heart failure, heart attack, and kidney damage. Knowledge is very important for hypertensive patients regarding blood pressure, with this knowledge can affect compliance with hypertension medication to control blood pressure, prevent chronic complications. The purpose of this study is to determine the relationship between knowledge level and medication adherence in hypertensive patients. This study uses a quantitative correlation method with a cross-sectional method. Data collection using the Accidental Sampling technique was carried out by distributing a knowledge level questionnaire and a medication adherence questionnaire (MARS-5-) on a sample of 269 people obtained from calculations using the Slovin formula that met the researcher's criteria. The results of the study using chi-square showed a significant p-value of 0.033. This shows that there is a relationship between the level of knowledge and medication adherence in hypertensive patients at the Rapak Mahang Tenggarong Health Center. It is expected that hypertension patients will continue to optimize their knowledge about hypertension and its treatment to control patients and increase awareness in hypertension management. And it is further improved regarding medication compliance to prevent complications such as kidney failure, heart failure, and stroke. This is because hypertension treatment is long-term or lifelong, by obediently taking medication can improve the patient's well-being.